2009
DOI: 10.1258/acb.2008.008095
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate laboratory utilization in diagnosing pulmonary embolism

Abstract: (1295) concerning studied patients were analysed. About 70.4% (93/132) of d-dimer tests were ordered in ED. In the studied patients, unfractionated heparin was administered in 17.8% (20/112) of the cases, low-molecular weight heparin in 79.5% (89/112) and heparin therapy was not administered in 2.7% (three of 112). Conclusion: This study uses a method to assess the quality of laboratory test orders using results as a tool to estimate the impact of economic resources devolved in executing inappropriate tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Thirty-eight studies investigated overutilization [15] , [17] [20] , [22] , [23] , [25] , [26] , [28] , [36] [63] ; eight investigated underutilization [25] , [45] , [48] , [57] , [64] [67] ; four investigated both [25] , [45] , [48] [57] . Thirty-one studies used objective criteria for measuring appropriateness [17] , [18] [22] , [23] , [26] , [28] , [37] , [38] , [40] [45] , [47] [49] , [52] , [54] [59] , [61] [67] while 11 used subjective criteria [15] , [19] , [20] , [25] , [36] , [39] , [46] , [50] , [51] , [53] [60] . Twenty studies investigated more than one test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-eight studies investigated overutilization [15] , [17] [20] , [22] , [23] , [25] , [26] , [28] , [36] [63] ; eight investigated underutilization [25] , [45] , [48] , [57] , [64] [67] ; four investigated both [25] , [45] , [48] [57] . Thirty-one studies used objective criteria for measuring appropriateness [17] , [18] [22] , [23] , [26] , [28] , [37] , [38] , [40] [45] , [47] [49] , [52] , [54] [59] , [61] [67] while 11 used subjective criteria [15] , [19] , [20] , [25] , [36] , [39] , [46] , [50] , [51] , [53] [60] . Twenty studies investigated more than one test.…”
Section: Resultsmentioning
confidence: 99%
“…sodium, glucose) [18] , [22] , [23] , [25] , [28] , [39] , [50] , [57] , [60] , [62] and complete blood count (hemoglobin, white blood cell count) [18] , [22] , [25] , [39] , [50] , [57] , [60] ; common disease monitoring tests (cholesterol, hemoglobin A1c) [45] , [50] ; tests of cardiac (creatine kinase) [18] , [50] , liver (transaminases, alkaline phosphatase) [18] , [23] , [25] , [39] , [50] , [54] , [62] , [63] , [65] , thyroid (thyroxine, thyroid stimulating hormone) [64] , and kidney function (blood urea nitrogen, creatinine) [18] , [22] , [23] , [25] , [39] , [50] , [57] , [60] , [62] , tests for anemia (iron, ferritin, B12, serum folate) [39] , [40] , coagulopathy (prothrombin time, partial thromboplastin time [PTT], protein C, protein S, D-dimer) [18] , [39] , [42] , [50] , [55] , [57] , ...…”
Section: Resultsmentioning
confidence: 99%
“…Over‐requesting of pathology tests is common in clinical practice with substantial associated economic costs . Studies in South Australian and Victorian hospitals, for example, found that 61% and 58% of tumour marker requesting is performed within hospital guidelines, respectively .…”
Section: Discussionmentioning
confidence: 99%
“…Previous pathology requesting patterns have been shown to depend on; (i) request form layout , (ii) clinician experience , (iii) communication between laboratory and clinic , (iv) referral base and (v) hospital policies . While anecdotal evidence suggests that over‐requesting may extend to the tests for detecting and monitoring M proteins in PCDs, to our knowledge, this is the first study analysing sFLC assay requesting patterns . In our study, we assessed use of the sFLC assay, adherence to guidelines published by the IMWG and likely causes of non‐adherence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation